Effect of replacing whole milk by skimmed milk on behaviour and health performances in crossbred dairy calves - THAMOTHIRAN K; P K BHARTI; G K GAUR; S A KOCHEWAD; TRIVENI DUTT (Indian Journal of Animal Sciences, 2020)
The study was aimed to investigate the impact of replacing whole milk by skimmed milk on behaviour and health performances in crossbred dairy calves. A total of 24 crossbred calves were allotted randomly into four groups, viz. Control (C), Treatment-1 (T1), Treatment-2 (T2) and Treatment-3 (T3) based on the birth weight and age. The calves in group C were fed on whole milk whereas skimmed milk was introduced to treatment groups at 22nd day of age @ 25, 50 and 75% of total liquid feed requirement for T1, T2 and T3, respectively. At 45th day of age, skimmed milk was fed @ 50, 75 and 100% of the total requirement, respectively for T1, T2 and T3 groups. From 64 to 72 days onwards calves were fed only on skimmed milk. The total time spent on standing, resting and moving in all groups were comparable. The total play time was significantly higher in T2 group than other groups. The fecal consistency score was significantly higher in T3 as compared to other groups. The blood parameters like hemoglobin, packed cell volume, total protein, albumin, globulin, creatinine and urea had varied significantly between the groups at some stages of experiment. The skimmed milk can replace the whole milk from 75 to 100% in early age of dairy calves without adversely affecting behavior and health performance.